The effects of a static and dynamic balance-training program in female volleyball players - Sawdon-Bea, J.; Sandino, N. (The Journal of Performance Enhancement, 2015)
Acute ankle injuries are prevalent in female volleyball players. Despite relatively mild severity and time away from sport, most individuals will experience recurrent sprains. Based on the high incidence rate of ankle injuries in female volleyball players, the purpose of this study was to determine the effects of a 6-week static and dynamic balance training program on self-reported disability and functional reach.